Combining protein-based biomaterials with stem cells for spinal cord injury repair. (2014) - A, Montgomery; A, Agbay; JM, Edgar; N, Gabers; J, Gomez; NK, Mohtaram; C, King; A, Mitchell; A, Rajwani; D, Rattray; M, Robinson; A, Shapka; et al.
No abstract available